2016
DOI: 10.1097/qai.0000000000000822
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Meningococcal Vaccination Among Men Who Have Sex With Men in New York City

Abstract: Vaccination during an IMD outbreak among MSM with and without HIV infection was projected to avert IMD cases and deaths and could be cost-effective depending on IMD incidence, case fatality, and herd immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“… 42 Among those with at-risk conditions, infection with VPDs resulted in a greater number of hospitalizations and an increased length of hospital stay compared to other at-risk patients without VPDs or healthy individuals. 42 , 43 , 46 These data indicate that VPDs cause a substantial clinical burden for both patients and HCPs and subsequently the healthcare system, which could be prevented by life-course immunization.…”
Section: Discussionmentioning
confidence: 94%
“… 42 Among those with at-risk conditions, infection with VPDs resulted in a greater number of hospitalizations and an increased length of hospital stay compared to other at-risk patients without VPDs or healthy individuals. 42 , 43 , 46 These data indicate that VPDs cause a substantial clinical burden for both patients and HCPs and subsequently the healthcare system, which could be prevented by life-course immunization.…”
Section: Discussionmentioning
confidence: 94%
“…A cost-effectiveness analysis, which accounted for herd immunity, found that vaccination was no longer costeffective when IMD incidence was fewer than 12/100,000 persons, using a threshold of US$100,000/QALY (2012 costs). 139 This analysis assessed vaccination during an outbreak of IMD among men who have sex with men with or without human immunodeficiency virus infection. A 2018 analysis, found that universal serogroup B vaccination was not cost-effective in college-aged young adults.…”
Section: Meningococcal Vaccinementioning
confidence: 99%
“…A cost-effectiveness analysis, which accounted for herd immunity, found that vaccination was no longer cost-effective when IMD incidence was fewer than 12/100,000 persons, using a threshold of US$100,000/QALY (2012 costs) ( 139 ). This analysis assessed vaccination during an outbreak of IMD among men who have sex with men with or without human immunodeficiency virus infection.…”
Section: Inactivated Vaccines In Patients With Inflammatory Bowel Diseasementioning
confidence: 99%